Carotenoides em abóboras - Veronezi, Carolina Médici [UNESP]; Jorge, Neuza [UNESP] (My University, 2011)
The present literature review highlights the importance of carotenoids as bioactive compound, and its potential application in functional foods. It were detailed the origin, chemical characteristics and sources of the carotenoids. It were also studied the most used methods to quantify and qualify the carotenoids, including spectrophotometry, mass spectrometry, high-performance liquid chromatography, gas chromatography and colorimetry. The pumpkin intake is recommended because they represent important source of carotenoids such as α-carotene, β-carotene and lutein.
Carotenoids in pumpkins
Keywords: Antioxidant; Carotenoids; Pro-vitamin A; Pumpkins; Cucurbita